2020
DOI: 10.1088/1757-899x/862/3/032053
|View full text |Cite
|
Sign up to set email alerts
|

Research of influence of errors of cam manufacturing on the law of motion of output element

Abstract: Insignificant error in the moment of manufacturing the mechanism can influence significantly on its’ work. Research of influence of manufacturing error with manufactured mechanism usually is irrational, that’s why necessity of evaluation at the stage of design occurs. Methods of evaluation of this influence are investigated in this paper. The research is implemented by developed algorithm, which also was realized in MATLAB and Python as well. Due this fact process of math simulation doesn’t occupy a lot of tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The choices for the cam manufacturing, such as the material, the production technology, the tolerances chosen in the design phase and the accuracy of the CNC machinery, can instead influence the follower law of motion. Samsonenko in 2020 in [26] researched the influence of errors of cam manufacturing on the law of motion of the output element and concluded that slight deviations of the cam shape from the ideal can lead to significant deviations of the movement's law of the follower. Therefore, a correct choice of the manufacturing method of the cam and of its tolerances is fundamental for the effectiveness of the proposed method.…”
Section: Introductionmentioning
confidence: 99%
“…The choices for the cam manufacturing, such as the material, the production technology, the tolerances chosen in the design phase and the accuracy of the CNC machinery, can instead influence the follower law of motion. Samsonenko in 2020 in [26] researched the influence of errors of cam manufacturing on the law of motion of the output element and concluded that slight deviations of the cam shape from the ideal can lead to significant deviations of the movement's law of the follower. Therefore, a correct choice of the manufacturing method of the cam and of its tolerances is fundamental for the effectiveness of the proposed method.…”
Section: Introductionmentioning
confidence: 99%